Generalized Mosaic Neurofibromatosis Type 1: A Rare Case Report - Parajuli, Niraj; Kayastha, Bhaskar MM; Shrestha, Rushma; Karki, Anupama; Lama, Laila (Birat Journal of Health Sciences, 2018)
Neurofibromatosis (NF) consists of group of genetically inherited disorders all of which is characterized by occurrence of nerve sheath tumors. There are eight different subtypes of neurofibromatosis. Segmental NF, a rare mosaic pattern of NF- type1 (NF1) is diagnosed in individuals who have typical features of NF1 restricted to one part of the body and whose parents are both unaffected. But recently the nomenclature has been changed to mosaic NF. We report a case of neurofibromatosis following the lines of blaschko. To the best of our knowledge, no such case report has been published till date of generalized mosaic NF following lines of blaschko's bilaterally symmetrically. BJHS 2018;3(1)5 :390-392